Climate change 2007 (Cambridge University Press, 2007)
The third volume of the Fourth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC) provides an in-depth analysis of the costs and benefits of different approaches to mitigating and avoiding climate change. It includes a detailed assessment of costs and potentials of mitigation technologies and practices, implementation barrier, and policy options for the sectors: energy supply, transport, building, industry, agriculture, forestry and waste management. This volume will be an essential reference to all those concerned with climate change, including students and researchers, analysts and decision-makers in governments and the private sector.